IN MEMORY OF THE PROFESSOR V.P. TULCHYNSKA - В. О. Іваниця; Т. В. Бурлака; Н. Г. Юргелайтic; Т. В. Гудзенко; Г. А. Кожанова; Л. Б. Котлярова (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2008)
The article is devoted to the centenery of the prominent scientist-microbiologist, corresponding member of NAS of Ukraine professor Vera Petrivna Tulchynska (31.07.1907 - 27.05.1994).The spectrum of scientific interests of V.P. Tulchynska was extremely wide and dealt with Medical, General and Water Microbiology, Virology, Ecology and Environmental Protection. V.P. Tulchynska has worked for 32 yeas (1951 - 1983) as the Head of the Chair of Microbiology and Virology of Odesa State University after I.I. Mechnykov.